2016
DOI: 10.1124/dmd.116.071100
|View full text |Cite
|
Sign up to set email alerts
|

VX-509 (Decernotinib)-Mediated CYP3A Time-Dependent Inhibition: An Aldehyde Oxidase Metabolite as a Perpetrator of Drug-Drug Interactions

Abstract: (R)-2-((2-(1H-pyrrolo [2,3-b]pyridin-3-yl)pyrimidin-4-yl)amino)-2-methyl-N-(2,2,2-trifluoroethyl)butanamide decernotinib) is an oral Janus kinase 3 inhibitor that has been studied in patients with rheumatoid arthritis. Patients with rheumatoid arthritis often receive multiple medications, such as statins and steroids, to manage the signs and symptoms of comorbidities, which increases the chances of drug-drug interactions (DDIs). Mechanism-based inhibition is a subset of time-dependent inhibition (TDI) and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…In fact, decernotinib is a selective inhibitor of JAK3 and phase 2 trials have shown efficacy in RA . However, decernotinib also exhibited CYP3A4‐mediated drug–drug interactions thereby affecting metabolism of statins and other drugs . PF‐06651600 is another selective JAK3 inhibitor being studied in RA, alopecia areata, CD, and UC (NCT02974868, NCT02958865, NCT02969044, NCT03395184).…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, decernotinib is a selective inhibitor of JAK3 and phase 2 trials have shown efficacy in RA . However, decernotinib also exhibited CYP3A4‐mediated drug–drug interactions thereby affecting metabolism of statins and other drugs . PF‐06651600 is another selective JAK3 inhibitor being studied in RA, alopecia areata, CD, and UC (NCT02974868, NCT02958865, NCT02969044, NCT03395184).…”
Section: Next‐generation Selective Jakinibsmentioning
confidence: 99%
“…[162][163][164] However, decernotinib also exhibited CYP3A4-mediated drug-drug interactions thereby affecting metabolism of statins and other drugs. 165 PF-06651600 is another selective JAK3 inhibitor being studied in RA, alopecia areata, CD, and UC 149,166 (NCT02974868, NCT02958865, NCT02969044, NCT03395184). Other JAK3-selective jakinibs are also in development.…”
Section: Jak3 Inhibitorsmentioning
confidence: 99%
“…These important clearance-contributing processes are often not first-order, yet they have only been described to a limited extent in AO. 20 , 21 , 35 , 45 Finally, inaccurate scaling between in vitro and in vivo clearance data has led to unanticipated rapid first-pass metabolism in several clinical trials, resulting in their failures. 22 , 24 , 27 A plausible explanation for AO clearance underprediction is that AO activity is not constant over the time of the incubation due to enzyme inhibition and/or inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то что «ведущий» цитокин (или цитокины), определяющие эффективность блокады JAK3 при ИВЗ, не известны, данные РПКИ фазы II свидетельствуют об определенных клинических перспективах селективного ингибитора JAK3 (децернотиниб) при РА [91][92][93]. Следует, однако, иметь в виду, что децер-нотиниб, взаимодействуя с CYP3A4, существенно влияет на метаболизм статинов и некоторых других часто применяемых в медицине лекарственных препаратов [94], что может ограничивать его применение у пациентов с ИВЗ с коморбидными заболеваниями. В настоящее время клинические исследования этого препарата приостановлены.…”
Section: таблицаunclassified